2017
DOI: 10.5545/sv-jme.2016.4272
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Thickness-to-Die Diameter Ratio on the Sheet Metal Blanking Process

Abstract: The blanking process has a wide range of usage in the sheet metal production industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Shear cutting of thick sheets, as used in truck frames, is challenging due to delaminations, which makes shear cutting parameters adapted to the sheet thickness essential [11]. This effect mainly occurs at larger die clearances and forms a starting location for further crack development.…”
Section: Introductionmentioning
confidence: 99%
“…Shear cutting of thick sheets, as used in truck frames, is challenging due to delaminations, which makes shear cutting parameters adapted to the sheet thickness essential [11]. This effect mainly occurs at larger die clearances and forms a starting location for further crack development.…”
Section: Introductionmentioning
confidence: 99%
“…They established a tolerance convergence percentage of 1 % and stated that an optimal clearance could be reached when the difference between crack angles satisfied this value, indicating that no secondary cracks occurred, and good surface quality was acquired. Engin and Eyercioglu [24] and [25] studied the influence of different process parameters on 1.4301 stainless steel sheets with different thicknesses and diameters. They observed that the best surface quality on the sheared workpieces was achieved when the difference between crack propagation angles was minimal.…”
Section: Resultsmentioning
confidence: 99%
“…The basic principle of monitoring the dimensional quality [16][17][18][19][20][21][22][23][24][25] is by monitoring the key characteristics (KC) [26] of a product. Which characteristics are KC and what are their codes, comes from the Control Plan of the product.…”
Section: Methodology Of Imog Modelmentioning
confidence: 99%